Introducing natural farming in black pepper (Piper nigrum L.) cultivation - Sulok, Kevin Muyang Tawie; Ahmed, Osumanu Haruna; Choy, Yuen Khew; Mercer Zehnder, Jarroop Augustine (Hindawi, 2018)
This paper reviews the role of Natural Farming as an ecological farming method to produce organically grown food of safe and high quality and at the same time improve soil quality and soil health. Currently, there is a dearth of information on the effects of Natural Farming approach on black pepper farms particularly in Sarawak, Malaysia. Previous studies on other crops had indicated positive outcome using the Natural Farming method. Thus, this paper discusses the essential role of effective microorganisms in Natural Farming and their potential in pepper cultivation. Through the action of effective microorganisms, this approach should be able to transform a degraded soil ecosystem into one that is fertile and has high nutrients availability. The mixed culture of effective microorganisms applied must be mutually compatible and coexist with one another to ensure its favorable establishment and interaction in the soil. Therefore, it is anticipated that introducing Natural Farming in black pepper cultivation can enhance the predominance of effective microorganisms in the soil, which in turn could lead to promising growth and yield of the crop.